Optimization of bioethanol production from seaweeds (Eucheuma spp.) - Tan, Pei Yee (2015)
The depletion of fossil fuels and increase in energy demand give rise to the urgent need to find a new alternative energy resource. The production of bioethanol using land-based and food crops have brought much controversy and debate on their sustainability. Respective to this, the use of marine biomass such as seaweeds in bioethanol production provides a possible solution for this energy issue. In this study, the potential for bioethanol production of the two species that abundantly found in Sabah, Malaysia: Eucheuma cottonii (Kappaphycus alvarezii) and Eucheuma denticulatum was studied by determining the amount of reducing sugars after acid hydrolysis as higher reducing sugars content will increase the potential of higher bioethanol yield. E. cottonii was selected due to the higher reducing sugars content and expected to produce higher bioethanol yield during fermentation. E. cottonii samples were hydrolysed by autoclave using sulphuric acid as catalyst with different acid concentrations (0.05-0.5 M), hydrolysis temperatures (110-130 °C) and hydrolysis time (5-25 minutes). The optimum conditions for hydrolysis were achieved at 0.1 M, 130 °C and 15 minutes. Before fermentation, the microscopic view and growth of yeast Saccharornyces cerevisiae were studied in the preparation of yeast inoculum. The yeast cells were harvested at the earliest exponential phase that is after nine hours of incubation. Subsequently, if. cottonii hydrolysates were fermented using different concentration of inoculum (10-30 v/v %) and fermentation time (12- 72 hours). Bioethanol content was quantified by using Gas Chromatography- Mass Spectrometry (GC-MS). The maximum bioethanol concentration (9.331 g/L) and bioethanol yield (0.164 g/g) were achieved at 20 v/v % yeast inoculum and 24 hours of fermentation duration. These results may provide useful information for development of more efficient methods for bioethanol production from seaweeds